Metabolism Plays a Key Role during Macrophage Activation. (10th December 2018) - Stunault, Marion I.; Bories, Gaël; Guinamard, Rodolphe R.; Ivanov, Stoyan
Abstract : Monocyte and macrophage diversity is evidenced by the modulation of cell surface markers and differential production of soluble mediators. These immune cells play key roles in controlling tissue homeostasis, infections, and excessive inflammation. Macrophages remove dead cells in a process named efferocytosis, contributing to the healthy tissue maintenance. Recently, it became clear that the main macrophage functions are under metabolic control. Modulation of glucose, fatty acid, and amino acid metabolism is associated with various macrophage activations in response to external stimuli. Deciphering these metabolic pathways provided critical information about macrophage functions.